Algoritma Apriori Untuk Memberikan Rekomendasi Menu Makanan Berdasarkan Tren Belanja Konsumen - Pusparisti, Myrtana; Paradhita, Astrid Noviana (STMIK Banjarbaru, 2025)
The increasing number of competitors means culinary businesses must innovate to increase their sales. Culinary businesses, especially Resto Sebelas Rasa, find it challenging to sell various food products. One strategy that can be applied is providing additional menu recommendations based on consumer purchasing trends. The additional menu recommendations must be by the menu segmentation that consumers have purchased in previous transactions. The Apriori algorithm can answer the need for innovation in the culinary business to increase sales levels for more varied food menus. The association rule algorithm can identify patterns of food menu combinations in the purchase transaction dataset. The Apriori algorithm calculates the support, confidence level, and lift values to determine how big the opportunity is and how strong the relationship is between food menu combinations. The Apriori algorithm has been successfully developed to increase the efficiency of consumer purchasing time by up to 90% and increase the variation in sales levels by up to 80%.Keywords: Segmentation; Buying trends; Apriori algorithm; Artificial intelligence AbstrakSemakin banyaknya kompetitor membuat bisnis kuliner harus berinovasi untuk meningkatkan penjualannya. Saat ini bisnis kuliner khususnya di Resto Sebelas Rasa merasa kesulitan menjual variasi produk makanan. Salah satu strategi yang dapat diterapkan yaitu memberikan rekomendasi menu tambahan kepada konsumen berdasarkan tren pembelian konsumen. Rekomendasi menu tambahan yang diberikan harus sesuai dengan segmentasi menu yang telah dibeli oleh konsumen pada transaksi sebelumnya. Algoritma Apriori dapat menjawab kebutuhan inovasi dalam bisnis kuliner untuk meningkatkan tingkat penjualan terhadap menu makanan yang lebih bervariatif. Algoritma asossiation rule dapat mengidentifikasi pola perpaduan menu makanan dalam dataset transaksi pembelian. Algoritma Apriori melakukan perhitungan terhadap nilai support, confidence level, dan lift untuk mengetahui seberapa besar peluang dan seberapa kuat hubungan perpaduan menu makanan. Algoritma Apriori berhasil dikembangan sehingga mampu meningkatkan efisiensi waktu pembelian konsumen hingga 90% dan meningkatkan variasi tingkat penjualan hingga 80%.